Einstein : his life and universe - Isaacson, Walter (Simon & Schuster, 2007)
The first full biography of Albert Einstein since all of his papers have become available shows how his scientific imagination sprang from the rebellious nature of his personality. Biographer Isaacson explores how an imaginative, impertinent patent clerk--a struggling father in a difficult marriage who couldn't get a teaching job or a doctorate--became the locksmith of the mysteries of the atom and the universe. His success came from questioning conventional wisdom and marveling at mysteries that struck others as mundane. This led him to embrace a morality and politics based on respect for free minds, free spirits, and free individuals. These traits are just as vital for this new century of globalization, in which our success will depend on our creativity, as they were for the beginning of the last century, when Einstein helped usher in the modern age.--From publisher description.